A NOVEL TECHNIQUE FOR FACE IDENTIFICATION - PROF. FEROZA MIRAJKAR; DR. RUKSAR FATIMA; PROF. K. B. PAWAR (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper presents a correspondence measure method based on novel method whichcombines a permutation of Voila Jones Face detection method and Eigen face recognition(Identification)technique. In the proposed method, we come to overcome the problem of low accuracy. We propose a new system here to align the face using Voila Jones Face detection method followed by Eigen face recognition technique. Compared to other face detection methods, the proposed method is very efficient for the face detection purpose. The system is built to meet real time face recognition criteria.